2019
DOI: 10.1111/apt.15477
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum interleukin‐2 after gluten correlates with symptoms and is a potential diagnostic biomarker for coeliac disease

Abstract: Summary Background Coeliac disease patients on a gluten‐free diet experience reactions to gluten, but these are not well characterised or understood. Systemic cytokine release was recently linked to reactivation of gluten immunity in coeliac disease. Aim To define the nature and time‐course of symptoms and interleukin‐2 changes specific for coeliac disease patients. Methods 25 coeliac disease patients on a gluten‐free diet and 25 healthy volunteers consumed a standardised 6 gram gluten challenge. Coeliac Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 30 publications
1
47
1
Order By: Relevance
“…personalized assessment of immune activation that was correlated with patient-reported outcome data. The present study complements two companion reports that describe assessments limited to only IL-2 in the same set of sera assessed in this study using a formally qualified electrochemiluminescence assay performed by a third-party vendor under good laboratory conditions [14,15]. IL-2 levels were always below the lower limit of quantitation (0·5 pg/ml) at all time-points in the healthy volunteers and also at baseline in the coeliac disease patients, but 23 of the 25 coeliac disease patients had elevated IL-2 levels 4 h after gluten [14,15].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…personalized assessment of immune activation that was correlated with patient-reported outcome data. The present study complements two companion reports that describe assessments limited to only IL-2 in the same set of sera assessed in this study using a formally qualified electrochemiluminescence assay performed by a third-party vendor under good laboratory conditions [14,15]. IL-2 levels were always below the lower limit of quantitation (0·5 pg/ml) at all time-points in the healthy volunteers and also at baseline in the coeliac disease patients, but 23 of the 25 coeliac disease patients had elevated IL-2 levels 4 h after gluten [14,15].…”
Section: Discussionmentioning
confidence: 53%
“…The present study complements two companion reports that describe assessments limited to only IL-2 in the same set of sera assessed in this study using a formally qualified electrochemiluminescence assay performed by a third-party vendor under good laboratory conditions [14,15]. IL-2 levels were always below the lower limit of quantitation (0·5 pg/ml) at all time-points in the healthy volunteers and also at baseline in the coeliac disease patients, but 23 of the 25 coeliac disease patients had elevated IL-2 levels 4 h after gluten [14,15]. Unlike ex-vivo or in-vitro assays with gluten-stimulated fresh blood cells, intestinal tissue, or particularly T cell lines and clones, cytokine assessments in serum are unlikely to be prone to significant laboratory artefact and, at least for IL-2, IL-8 and IL-10, appear to be consistent findings after injection of deamidated gluten peptides and for food challenges with 3 or 6 g of gluten protein, and gluten ingested in a variety of formats, such as bread or as vital gluten added cooked in muesli bars, or uncooked in the format used in the present study [1].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the three phase 1 studies, which have been reported in detail elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet had no study interventions before their pre‐treatment biopsy. In the phase 2 (‘RESET CeD’) trial, which has also been described elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet, but had a single bolus gluten challenge (6 g of gluten protein taken as 10 g vital wheat gluten flour in water) 3 weeks before biopsy collection according to the protocol described by Tye‐Din et al…”
Section: Methodsmentioning
confidence: 99%
“…These include nocebo effects, where patient's negative expectations to potential gluten exposure influence their symptoms and the presence of non-gluten dietary components such as fermentable carbohydrates (FODMAPs) that can cause symptoms of irritable bowel syndrome (IBS) independent of gluten [4,5]. In several recent gluten food challenge studies in small groups of patients with treated CD, unmasked and also double-blind, sham-controlled gluten challenges designed to be low in FODMAPs cause significant worsening of nausea, sometimes with vomiting, within 2-h and peak at 3 to 4 h, but rarely caused diarrhoea [6,7]. This acute symptomatic reaction to gluten in patients with treated CD is linked to significant concomitant elevations in serum cytokines, which are not observed in individuals without CD or those with self-reported non-CD gluten sensitivity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%